(untitled) (Medicine Today, 2017)
A prospective interventional self-control study to see the outcome of suture less and glue free limbal conjunctival autograft for the management of primary and recurrent pterygium was carried out using patient’s own blood as a bio-adhesive to secure the graft in position, in the Department of Ophthalmology, 250 bedded General Hospital Jamalpur from 15.09.16 to 30.11.16 and followed up upto July 2017. A total of 48 cases (44 were primary nasal pterygium and 4 were recurrent pterygium) were included in the study. Regarding type of the pterygium, out of 48 patients 3(6.25%) were grade I, 21(43.75%) were grade II, 13(27.08%) were grade III and 11(22.92%) were grade IV. The mean age of the study population was 32±2 years. The male and female distribution was 18 and 30 respectively. All the eyes followed by bandaging for 24-48 hours and were examined for graft dislodgement, recession, edema sub-conjunctival hemorrhage. Out of 48 eyes only 1 (2.1%) had sub-conjunctival hemorrhage, 2 (4.2%) edema and 3 (6.3%) had graft recession after 24 to 48 hrs of operation. All the complications were resolved 1-2 month. There was no recurrence of pterygium. No recurrence, graft loss or granuloma was recorded. No other complication was noted. Suture less and glue free limbal conjunctival autografting following pterygium excision is an effective and safe option for the management of primary pterygium. Medicine Today 2017 Vol.29(2): 46-50